2016
DOI: 10.1371/journal.pone.0149537
|View full text |Cite
|
Sign up to set email alerts
|

The Angiogenic Effect of microRNA-21 Targeting TIMP3 through the Regulation of MMP2 and MMP9

Abstract: microRNAs are a novel set of small, non-protein-coding nucleotide RNAs that negatively regulate the expression of target mRNAs. miRNA-21 is a microRNA that is highly enriched in endothelial cells. miRNA-21 has been shown to be a potential pro-angiogenic factor in some biological systems. Our previous study showed that the expression of miRNA-21 was up-regulated after spinal cord injury. However, the effect of miRNA-21 on angiogenesis in the spinal cord was unclear. In this study, to understand the role of miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 53 publications
2
62
0
Order By: Relevance
“…A previous report has indicated that the angiogenic effect of miR-21 acts by targeting TIMP3/MMP signaling 20 . Moreover, TIMP3/MMP9 signaling plays an important role in regulating vascular permeability 21 , 22 .…”
Section: Resultsmentioning
confidence: 99%
“…A previous report has indicated that the angiogenic effect of miR-21 acts by targeting TIMP3/MMP signaling 20 . Moreover, TIMP3/MMP9 signaling plays an important role in regulating vascular permeability 21 , 22 .…”
Section: Resultsmentioning
confidence: 99%
“…The expression of miR-126-5p enhances angiogenesis by repressing the expression of Spred-1, an intracellular inhibitor of angiogenic signaling, leading to enhanced signaling of angiogenic growth factors including VEGF and FGF 33 . MiR-21-5p promote angiogenesis partly through directly targeting TIMPs leading to enhanced VEGF signaling and endothelial cell migration 34 . Together with our observation of reduced expression of VEGF and FGF-β in tumor tissues, it suggests that an anti-angiogenic activity may be involved in the tumor inhibitory effect of Arc.…”
Section: Discussionmentioning
confidence: 99%
“…TIMP-3 is sequestered to ECMs, whereas all other TIMPs (TIMP-1, 2, and 4) are present in the soluble forms (Baker et al, 2002). Previous studies have been shown that TIMP-3 regulates the activities of MMPs, such as MMP-2, -7, -9, and -13 (Deb et al, 2015;Fu et al, 2016;Hu et al, 2016;Yamamoto et al, 2016). Herein, we also showed that S1P inhibits cell migration mainly by downregulation of MMP-2, but partially by MMP-7, -9, and -13.…”
Section: Discussionmentioning
confidence: 99%
“…3.3. S1P induces TIMP-3 expression through downregulation of microRNA (miRNA)-101 expression in human chondrosarcoma cells MicroRNA (miRNA) was shown to play important roles in the regulation of cancer progression and metastasis (Chen et al, 2015a;Hu et al, 2016;Nugent, 2015;Tsai et al, 2015). To investigate whether miRNA is responsible for the S1P-induced TIMP-3 expression, 12 predicted miRNA that contain binding sites of the 3 0 UTR of TIMP-3, identified by Targetscan (http://www.targetscan.org/), were studied.…”
Section: S1p Inhibits Mmp-2 Expression Through the Upregulation Of Timentioning
confidence: 99%